Pengaruh Variasi Stuktur Rangka Terhadap Kekuatan Pembebanan Pada Stasiun Pengisian Daya Listrik dengan Panel Surya - Ade Suparman; Ade Sunardi; Mohamad Zaenudin (Integrated Mechanical Engineering Journal, 2023)
The use of solar panels in electric power charging stations is becoming increasingly popular as part of efforts to adopt renewable energy sources. In this context, the structural framework supporting the solar panels plays a crucial role in maintaining the stability and reliability of the system. Therefore, this thesis aims to investigate the influence of various structural framework variations on the strength of static loading in solar-powered electric charging stations. The research methodology employed simulation of static loading at three different load levels, namely 40 kg, 50 kg, and 60 kg. The analysis was conducted by comparing the equivalent stresses and total deformations between "Design 1" and "Design 2" at each load level. The research findings reveal significant differences in equivalent stresses and total deformations between the two designs at each load level. Design 1, with a stiffer structural framework, exhibited higher equivalent stresses and greater total deformations compared to Design 2. Consequently, this study provides a deeper understanding of the influence of various structural framework variations on the strength of static loading in solar panel support structures. These findings can serve as a basis for optimizing the structural design of solar-powered electric charging systems.